FASILITAS PENGELOLAAN SAMPAH ORGANIK DAN NON ORGANIK UNTUK MENINGKATKAN KESADARAN LINGKUNGAN BERSIH - Cahya Febrina, Sindy; Ryan Gerry Patalo; Eko Yuni Prihantono; Putra Pratama Supriyanto (Universitas Kadiri, 2025)
Cleanliness is an important aspect of daily life, from personal hygiene to environmental cleanliness. Cleanliness can reflect the health of each individual. Personal hygiene includes regular bathing, washing clothes, and brushing teeth daily. Environmental cleanliness refers to the surrounding environment where humans live, including the home environment, the interior of the house, and public places around people. This activity aims to provide knowledge about the impacts of waste and how to handle it, as well as provide supporting facilities. The implementation method for this community service included outreach and interviews. The activity was attended by the waste operations team, the youth organization head, the local neighborhood association head, and residents of Sawun Hamlet. The result of this activity was the provision of warning signs, increasing community awareness of practicing clean living behaviors and being able to distinguish between organic and non-organic waste.